Tendon Transfers for Peroneal Nerve Injuries in the Multiple Ligament Injured Knee - Irgit, Kaan Suleyman; Cush, Gerard (The Journal of Knee Surgery, 2012)
Although knee dislocations are relatively rare injuries; associated drop foot complication as a consequence of common peroneal nerve palsy (CPN) is substantially high. Even after successful ligament constructions; unresolved CPN palsy is a factor contributing to bad outcome after knee dislocations. CPN palsy is seen more after open dislocations, rotatory dislocations, and especially in patients with posterolateral corner injuries. CPN palsy can readily be diagnosed clinically, although high index of suspicion is needed. Surgical exploration in the acute setting is still debatable. Conservative management can be appropriate in early phase of treatment, however surgery is the choice of treatment for persistent nerve damage. Neurolysis, primary nerve repair, nerve grafting, and posterior tibialis tendon transfer are all reasonable choices for surgical treatment. Late surgery results have an exceedingly low success. Tibialis posterior tendon transfer is indicated primarily in the setting of a drop foot and a steppage gait. Tibialis posterior tendon transfer procedures have had acceptable success in allowing patients to return to ambulation without assistive device.
Keywords: peroneal nerve palsy; drop foot; posterior tibial tendon; knee dislocation; tendon transfer